Brexit and Indirect Impact Routes through Global Value Chains - Jyrki Ali-Yrkkö; Tero Kuusi (The Research Institute of the Finnish Economy (ETLA), 2019)
In this study, we analyze the trade linkages between the United Kingdom (UK), Finland, and the European Union (EU). We calculate the value-added content of trade through complex global value chains (GVCs), which may involve numerous production stages and third countries. Our results show that the importance of the UK as a trading partner for Finland has decreased during the last 15 years, and the tendency has been stronger than that between the UK and other EU countries, on average. We compare the importance of the UK to that of other countries by extracting the total amount of the Finnish value added that is generated in the value chains involving individual countries. Through this comparison, we find that the UK ranks as the sixth most important country. We further decompose the total value added into components that quantify the value added that is generated through direct trade with the UK and the indirect trade that is channeled through third countries. We find that roughly one third of the total value added is generated through indirect trade and two thirds through direct trade. Our analysis also suggests that one fifth of both the Finnish and EU value-added trade to the UK passes through the UK to other countries. The main destination countries are the United States (US), Germany, and France.
Keywords: F13; F14; F23; L23; 330; Global value chain; Brexit; United Kingdom; Gross domestic product; Impact; Indirect; Route; Value added